Development of a GIS Tool to Find Fiber Cable Fault Using Python Scripting for ArcGIS in Amman City - Shehadeh, Madeleine Taiseer; Al-Qaralleh , Mohammed Jamil (Jordan Journal of Social Sciences, 2024)
Optical fiber cables are characterized by a larger bandwidth than other transmission media, which increases the amount of data transmitted per unit of time. Managing a fiber optic network using Geographic Information Systems (GIS) has benefits for the operation and maintenance of the communication network. The study aims to develop a GIS tool to detect fiber optic cable faults using Python Scripting for ArcGIS in the city of Amman. To achieve this goal, the Esri data model for telecommunications was used. The study concluded that it is possible to locate faults using the Python programming language, and the program provides accurate coordinates based on the precision of the OTDR device.